Policy Analysis of Regional Public Service Agencies (BLUD) at H. Andi Sulthan Daeng Radja Hospital Bulukumba Regency - Faizah, Andi; Haanurat, Ifayani; Ibrahim, Juliani (Proceeding UII-ICABE, 2020)
This study aims to determine the implementation of the policy, the form of financial management patterns, the level of success of work unit performance (SATKER) in H.A. Sulthan Daeng Radja Hospital, Bulukumba Regency after the BLUD application. This research was conducted at H.A. Sulthan Daeng Radja Hospital in Bulukumba Regency using qualitative methods with data collection techniques through observation and in-depth interviews with representatives of BLUD officials, ASN and Non ASN BLUD satker selected purposively. The results of this study indicate that the implementation of the policy is not optimal based on Permenkes No. 20 of 2014, the form of financial management is guided by government policies as stipulated in the Act, but the implementation is not optimal, because the factors forming organizational structure are not based on expertise and skills, lack of support from satker, financial management is not optimal, does not reflect healthy business practices, no transparency, no financial performance assessment sheets are made, procurement management is not good, achievement of Minimum Service Standards (SPM) is still below the target and evaluation of the success rate of BLUD satker performance is still low. Kata Keywords: BLUD, Policy, Implementation, Financial BLUD